Readability Analysis of Rancagé Diajar Basa Sunda for Junior High Schools: Evidence from the Fry Graph - Tanti Sri Wahyuni; Nunuy Nurjanah; Haris Santosa Nugraha (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to analyze the readability level of 43 texts in the book Rancagé Diajar Basa Sunda for junior high school students using Fry Graphs, as well as to evaluate their suitability for readers aged 12 to 15 years. This study uses a document analysis method comprising steps such as text identification, calculation of sentence and syllable counts, graph mapping, and interpretation of results in the context of Sundanese. The results showed that only 11 texts (26%) were in the